Percutaneous drainage for hinchey Ib and II acute diverticulitis with abscess improves outcomes - Rosen, David R.; Pott, Emily G.; Cologne, Kyle G.; Lee, Sang W.; Ault, Glenn T.; Grabo, Daniel J.; Clark, Damon H.; Strumwasser, Aaron M. (Turkish Journal of Gastroenterology, 2019)
Background/Aims: The role of percutaneous drainage in Hinchey Ib and II diverticulitis is controversial. The aim of the present study was to clarify the indications for percutaneous drainage in such circumstances.Materials and Methods: This was a single-center retrospective review at an academic tertiary care hospital. All Hinchey Ib and II diverticulitis cases admitted from 2012 to 2014 were considered. Results: Overall, 104 (78%) patients underwent successful conservative treatment, whereas 30 (22%) patients underwent surgery during admission. During the index admission, abscess drainage was performed in 21 patients, of which 19 patients were successfully managed without surgery on the index admission and two patients ultimately required surgery. Elective versus same-admission surgery resulted in an increase use of laparoscopy (p=0.01), higher rate of restoration of gastrointestinal continuity with the index operation (p=0.04), and lower rate of diverting stoma formation (p<0.01). Conclusion: Percutaneous drainage may diminish the need for emergent surgery for Hinchey Ib and II diverticulitis. Elective surgery following conservative management increases the use of laparoscopy and decreases the rates of stoma formation.